Relationship Of Mom's Knowledge About Delivery Technique And Perineum Rupture In Normal Delivery At The Yani Delitua Midwife Clinic In 2022 - Rini Febrianti (International Archives of Medical Sciences and Public Health, 2022)
Normal delivery is the process of expelling the products of conception that have been enough months, born spontaneously with a back of the head presentation that takes place within 18 hours, without complications to both the mother and the fetus. Pregnant women are really looking forward to the arrival of the time of delivery, because they crave the presence of the baby who has been waiting for 40 weeks. The formulation of the problem in this study is "Is there a relationship between maternal knowledge about straining techniques and perineal rupture in normal delivery at the Yani Delitua Midwife Clinic in 2022. The research design in this study was an analytic survey with a cross sectional approach. In this study, the relationship between the independent variable (mother's knowledge) and the dependent variable (perineal rupture) at the Midwife Yani Delitua Clinic in 2022 was studied. The sample in this study from March to May 2022 was 37 people. Sampling used a non-probability sampling approach and the sampling technique in this study was accidental sampling. There is a significant relationship between mother's knowledge of pushing techniques and perineal rupture at the Yani Delitua Midwife Clinic in 2022 with p = 0.043 <0.05. Suggestions to respondents to seek more information to increase their knowledge, especially about pushing techniques to avoid perineal rupture on the internet, health workers, and so on.